Biodiesel do dendê: um estudo de viabilidade econômico financeira no Estado do Pará - Castro Junior, Augusto Gomes (2012)
The goal of this study is to analyze three operational models of an extraction plant of palm oil, palm kernel oil and biodiesel, respectively, together with palm oil production by family agriculture looking forward the exclusive supply of raw material to the industry through a partnership established by the National Program of Family Agriculture ('Programa Nacional da Agricultura Familiar'). The project consists in the construction of a large-scale production plant financed with public and private investments applied in the construction of an industrial complex and in the funding of the implementation of cultivation of palm oil by the farmers. Four scenarios were constructed, in which were evaluated economic performance indicators of the financial assessment of the productive arrangement and the agricultural industry. These scenarios aim the investment decision making through the use of classic economic indicators to assess the viability of palm oil as a raw material for the plant’s industrial complex. Among the indicators used in the work we can cite as main NPV (Net Present Value) and IRR (Internal Rate of Return), and as secondary indicators, used as support for the analyzes, indicators such as Discounted Payback, MIRR (Modified Internal Rate of Return) among others. Besides social indicators like potential of income generation for the farmers families, with the main objective of creating monetary value, generate employments, income and payment of public investor’s resources applied. The implementation of palm oil culture is based on the Agroecological Zoning of the Palm and will be implemented in areas degraded by grazing to ensure sustainability to contribute to the environmental recovery through carbon sequestration, and to reduce the pressure on native forests. Consequently, the project is expected to contribute to prevent the advance of deforestation in the Legal Amazon region. In order to do so, visits were carried out to palm oil plantation and to Biopalma plant. Also visits were carried out to Western Embrapa, located in the city of Manaus, and Embrapa located in the city of Campinas. An economic analysis model, based on the implementation of a Biodiesel large scale production plant, located in the State of Pará, was proposed. Among its limitations, the study could classify its complexity and broadness; the inexistence of available large-scale plant projects fully implemented and operating with the use of technology and intensive capital; and also the inability to conduct this research in a broad spectrum without considerably larger number of organizations involved. As result, the economic indicators show that there is analyzed viability of the project in three of the four scenarios constructed, demonstrating that the equity investor public, private and family farmers will be paid using interest rates, terms, conditions of capital markets. The goal is to attract investments for the production of biodiesel, implementation of agricultural enterprises, industrial, employment and income generation for Family Farming in the supply chain of palm oil.